Validation of University of Ibadan teaching practice evaluation Instrument (2020)
The purpose of this study was to validate and determine the psychometrics properties of Teaching Performance Assessment Rating Scale (TPARS) an instrument that is been used in the assessment of teachers in training in University of Ibadan. The TPARS is a 20-item inventory which assesses teaching performance among education students in university of Ibadan. Three research questions were raised to guide the study.The results of the TPARS analysis reveal that the instrument of teaching performance skills comprises of six dimensions namely:Teachers in training preparation, Making Learners Ready and Progression, Communication and Teachers in training pupils interaction, Assignment, Grading Praise and Rewards, Classroom Atmosphere, Subject mastery and Instructional materials and Teachers in training demeanor. The researcher further tested whether the TPARSis tenable using confirmatory factor analysis. The result of Confirmatory Factor Analysis provides a good fit of the data within the hypothesized six-factor model, implying that the TPARS can be subsumed into six domains. Discriminant and Convergence validities were moderate ranging from .31 to .69. Alpha coefficients for six TPARS subscales ranged from .81 to .96, and .79 for the whole scale. The findings highlighted the importance of using indigenous instrument in identification of factors underpinning teaching performance among teachers in trainee. The study recommends the TPARS for other higher institutions to assess their teachers in training so that all higher institutions in Nigeria could have single and uniform instrument for assessing teaching performance skills of student-teacher.